Discussion - Of Mr. Lee's Paper on The Corrosion of Water-Jackets of Copper Blast-Furnaces (see Trans., xxxviii., 877) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
C. D. Demond, Anaconda, Mont. (communication to the Secretary*) :—In order to throw some light on this interesting subject, a series of experiments were made with strips of mild steel, containing about 0.14 per cent. of C and 0.22 per cent. of Ma. These strips were thoroughly cleaned and brightened before use, salts were added to distilled water until it corresponded as nearly as possible to the analysis given by Mr. Lee, and in this water at different temperatures were placed four strips of steel; while four other strips, at corresponding temperatures, were placed in the water used at the Washoe Reduction Works. The latter plant has had no trouble from corrosion of furnace-jackets, pipe-lines or boilers. The analysis of the water used at the Washoe works is: Grains er U. S. Gallon. CaCO3........... 2.92 CaSO3........... 0.76 MgCI3........... 0.64 MgCO3........... 0.58 A1203........... 0.12 Fe2O3........... 0.12 SiO2........... 0.58 NaCl........... 0.35 Organic matter, etc.,........ 1.16 7.23 This water is neutral to litmus; while the artificial Copper Queen water was very slightly alkaline, which Mr. Lee informs us is also true of the water at Douglas. Both waters mere well aerated by pouring from beaker to beaker, and by blowing in air from the experimenter's lungs. The results of these tests, given in Table I., show that there is no significant difference between the effects of the two waters.